NAO and jet indices - Tess Parker; Tim Woollings; Antje Weisheimer; Laura Baker; Christopher O'Reilly; Len Shaffrey (2018)
This fileset provides the seasonal NAO indices and the jet latitude and jet speed indices for the ERA-Interim and ERA-20C reanalyses, and the ASF-20C, SEAS5 and GloSEA5 (CS3) seasonal re-forecasts. The methodology is described in the article "Seasonal predictability of the winter North Atlantic Oscillation from a jet stream perspective".